Analysis of the Supply of Sport Services by Organizational Aspects - Bácsné Bába, Éva; Fenyves, Veronika; Dajnoki, Krisztina; Szabados, György Norbert (International Journal of Engineering and Management Sciences, 2018)
The spread of consumer societies has led to the commercialization, and the emergence of profit-oriented operating frameworks in the fields of sport. The sports enterprises, involved in the operation of competing groups on professional, spectator fields of sport have already been examined from legal, economic, organizational points of view by a number of international and Hungarian researchers. In this article, we attempt to cover and summarize the Hungarian research approaches on this subject. The motive behind our investigation is that we should launch an organizational examination of the Hungarian profit-oriented sports suppliers in the near future. We plan to analyse the property, financial, income, organizational, management and labor management related situation of these sports enterprises. In order to ground the research, the review nature summary of domestic economic, organization science related secondary examinations is essential, which allows the development of the appropriate research methodology and the comparison of our results with the antecedents.